Use of Arduino Microcontroller and Proteus Software in Physics Lesson in Review of Mathematics Ability and Critical Thinking Skills - Matsun Matsun; Boisandi Boisandi; Ira Nofita Sari; Soka Hadiati; Sy Lukman Hakim (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to determine the effect and interaction of the use of learning media, mathematical abilities, and critical thinking skills on student achievement. The design of this research is experimental. Data were analyzed using a three-way ANOVA analysis of variance. The results showed: 1) there was an effect of cognitive and affective learning achievement of students who were given learning using Arduino microcontroller and Proteus software, but there was no effect on psychomotor learning achievement; 2) there is an effect of cognitive learning achievement of students who have high and low mathematical abilities, but there is no effect on affective and psychomotor learning achievement; 3) there is no effect on cognitive and affective learning achievement of students who have high and low critical thinking skills, but there is an effect on psychomotor learning achievement; 4) there is no interaction between the inquiry model using Arduino microcontroller and Proteus software with mathematical ability on students' cognitive, affective and psychomotor learning achievement; 5) there is no interaction between the inquiry model using Arduino microcontroller and Proteus software with critical thinking skills on student cognitive and psychomotor learning achievement, but there is an interaction on student affective learning achievement; 6) there is no interaction between mathematical ability and critical thinking skills on student achievement; 7) there is no interaction between the inquiry model using Arduino microcontroller and Proteus software, mathematical ability, thinking skills on student achievement.